2014
DOI: 10.1007/978-3-662-44303-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Learning Dynamical Systems Using Standard Symbolic Regression

Abstract: Abstract. Symbolic regression has many successful applications in learning free-form regular equations from data. Trying to apply the same approach to differential equations is the logical next step: so far, however, results have not matched the quality obtained with regular equations, mainly due to additional constraints and dependencies between variables that make the problem extremely hard to tackle. In this paper we propose a new approach to dynamic systems learning. Symbolic regression is used to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…It has been shown that symbolic regression can generate ordinary nonlinear partial differential equations for nonlinear coupled dynamical systems 46,68 as well as approximate ordinary differential equations. 69 Meanwhile, it is also often of desire to find conservation laws in physical systems. The ability to unearth conservation laws with symbolic regression goes beyond the aim of materials property predictions and helps researchers establish insight into the materials systems they study.…”
Section: B Opportunities In Materials Sciencementioning
confidence: 99%
“…It has been shown that symbolic regression can generate ordinary nonlinear partial differential equations for nonlinear coupled dynamical systems 46,68 as well as approximate ordinary differential equations. 69 Meanwhile, it is also often of desire to find conservation laws in physical systems. The ability to unearth conservation laws with symbolic regression goes beyond the aim of materials property predictions and helps researchers establish insight into the materials systems they study.…”
Section: B Opportunities In Materials Sciencementioning
confidence: 99%
“…When performing symbolic regression, candidate solutions are usually represented as trees, where the terminal nodes (also called "leaves") correspond to constants and variables, and where all the other nodes encode mathematical functions (primitives) [13]. In this work vectors, representing, in a dot add k1 k1 dot k1 X_vec…”
Section: Symbolic Regressionmentioning
confidence: 99%
“…Genetic programming [17] is a collection of methods for the automatic generation of computer programs that solve carefully specified problems, via the core, but highly abstracted principles of natural selection. The organisms that undergo adaptation are in fact mathematical expressions (models) for the surface porosity of hardened Figure 12.…”
Section: Solution Of Problemmentioning
confidence: 99%